Analisis Sistem Pemerintahan Desa Adat Ammatoa dalam Pelestarian Lingkungan Hidup di Kecamatan Kajang, Kabupaten Bulukumba - Ade Rezkiawan Embas; Jayadi Nas (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2017)
This study was conducted with the aim to describe the system of Ammatoa traditional village administration in environmental conservation by looking at how the implementation of customary governance system in conservation of environment of Kajang in Bulukumba Regency. The research type used is descriptive analysis that is a sudden that gives social picture systematically, Factual and accurate data obtained in the field. Data collection is done by using observation, interview and documentation techniques. The results of this study indicate that: Firstly, the implementation of environmental conservation of Ammatoa custom area by using Ri Kajang as customary law as a guide and regulation still effective in implementing forest protection and environment of tidal regulation still very adhered by indigenous people, and with regulation District of Bulukumba Number 9 Year 2015 on Inauguration, Recognition of Rights, and Protection of Rights that strengthen the protection of customary territories. Second, live the customary forest. The inhibiting factor of enforcing regulations in Ammatoa's environmental protection is the insistence of outsiders who begin to come in with modernity and social change that begin to erode the indigenous Ammatoa